2015
DOI: 10.4103/0971-3026.169454
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of endovascularly managed iatrogenic renal hemorrhages

Abstract: Objective:To evaluate the effectiveness of endovascular management in iatrogenic renal injuries with regard to clinical status on follow-up and requirements for repeat angiography and embolization.Materials and Methods:This retrospective study included patients who were referred for endovascular management of significant hemorrhage following an iatrogenic injury. Data was recorded from the Picture Archiving and Communication system (PACS) and electronic medical records. The site and type of iatrogenic injury, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 27 publications
1
7
1
Order By: Relevance
“…As reported by Chiramel et al, embolization was performed in 53 patients with the manifestation of RAP or RAVF in the first renal angiography, of which 38 (71.7%) showed clinical resolution. [ 17 ] Incomplete embolization with coils may explain the relatively lower resolution rate compared with that in our study. In another study including 21 patients receiving TAE for iatrogenic arterial kidney bleeding, Ierardi et al reported that the technical success rate was 100% and overall clinical success rate was 95%, which was in agreement with our results.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…As reported by Chiramel et al, embolization was performed in 53 patients with the manifestation of RAP or RAVF in the first renal angiography, of which 38 (71.7%) showed clinical resolution. [ 17 ] Incomplete embolization with coils may explain the relatively lower resolution rate compared with that in our study. In another study including 21 patients receiving TAE for iatrogenic arterial kidney bleeding, Ierardi et al reported that the technical success rate was 100% and overall clinical success rate was 95%, which was in agreement with our results.…”
Section: Discussioncontrasting
confidence: 68%
“…[ 7 ] In another retrospective series of patients with iatrogenic renal hemorrhages, no significant change in serum creatinine level was observed after embolotherapy. [ 17 ]…”
Section: Discussionmentioning
confidence: 99%
“…Technical success rates of 98%–100% and clinical success rates of 83%–98% for endovascular management of renal vascular injuries have been reported, similar to ours. [ 13 14 15 ] Endovascular management has high success rates with fewer complications, rapid recovery, and a better safety profile as compared to surgery. Complications can be due to access site aneurysm, hematoma or dissection, renal artery dissection or perforation, non-target embolization, and rarely significant parenchymal loss causing hypertension or even renal failure.…”
Section: Discussionmentioning
confidence: 99%
“…Alternative follow-up investigations could include ultrasound with colour doppler (might show active bleed into a haematoma) or CT-angio to detect the cause of the continual bleed. 17 Selective RAE will also infarct areas of healthy renal tissue. However, our review did not show a significant loss of global renal function (based on serum creatinine levels).…”
Section: Discussionmentioning
confidence: 99%